Screening of Some Microalgae for Astaxanthin - Bhat, Aakriti (My University, 2017)
Present work was focused on screening of astaxanthin content in three different algal species Haematococcus pluvialis, Chlorella vulgaris and Anabaena variabilis. Growth was studied in terms of biomass for all species and cell count in Haematococcus pluvialis and Chlorella vulgaris in BG11. Haematococcus pluvialis produced highest biomass of 0.867 mg/ml with 0.015% astaxanthin content. Haematococcus pluvialis and Chlorella vulgaris producing higher amounts of astaxanthin were grown in two different media BG11 and BBM under indoor and outdoor conditions. Haematococcus pluvialis in BG11 gave maximum biomass yield of 0.6 mg/ml and astaxanthin content of 0.006% under indoor cultivation whereas 4.276 mg/ml biomass and 0.096% astaxanthin under outdoor cultivation. Among three different microalgae, astaxanthin content was higher in Haematococcus pluvialis followed by Chlorella vulgaris and Anabaena variabilis.
Master of Technology -Biotechnology
Keywords: Microalgae; Astaxanthin; Biomass; Cell Count